PRELIMINARY PHYTOCHEMICAL SCREENING, CHARACTERIZATION, AND ANTIDIABETIC ACTIVITY OF LEAF EXTRACT OF CANNA INDICA L. IN STREPTOZOTOCIN-INDUCED DIABETIC MODEL - YADAV, PRASHANT KUMAR; SS, SISODIA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study aimed to evaluate the antidiabetic effects of the leaf extract of Canna indica L. in streptozotocin (STZ)-induced diabetic model. The present investigation indicated that the leaf of C. indica L. possessed significant antihyperglycemic potential which may prove the claimed use of the plant in amelioration of diabetes. Methods: Male Swiss albino mice fasted for 12–14 h and weights were recorded prior to the induction of diabetes. Experimental diabetes was induced by a single intraperitoneal injection of 150 mg/kg of STZ, freshly dissolved in 0.1 M citrate buffer (pH=4.5). Then, the solution was immediately administered intraperitoneally to each mouse. Thirty minutes after the injection, the mice were allowed free access to food and water. After 6 h STZ injection, mice were given a 5% dextrose solution for the next 24 h. The development of diabetes was confirmed after 3 days of the STZ injection and mice with fasting blood glucose level (BGL) >200 mg/dl were considered as diabetic and were selected for the experiments. After successfully developing the diabetes animals were divided into six groups and each group contains six mice. Group I: Normal control mice administered vehicle only; Group II: Diabetic control mice administered vehicle only; Group III: Tested mice administered glibenclamide 5 mg/kg; and Group IV–VI: Tested mice administered C. indica L. at doses of 100, 200, and 400 mg/kg, respectively. All groups received treatments once daily for 14 days. The fasting BGL and body weight were determined at 0, 7th, and 14th days. Results: The effect of C. indica L. on BGL having significant (p<0.05 and p<0.001) reduction in BGL starting 1 h when compared to the negative control. Administration of glucose (2 g/kg) to the mice produced significant (p<0.001) increase in BGL 30 min following 1 h after glucose loading, confirming the induction of hyperglycemia. The extract with three doses (100, 200, and 400 mg/kg) showed a significant reduction in BGL. The phytochemical screening of the leaves extract was done for the presence of alkaloid, saponin, terpene, carbohydrate, steroid, protein, cholesterol, flavonoids. Amino acid was absent in C. indica L. leaves. Conclusion: It is concluded from this study that the alcohol extracts of C. indica L. leaves possess significant antihyperglycemic effects.